APPLICATION MEMBRANE DISTILLATION FOR ZERO LIQUID DISCHARGE (ZLD) DESALINATION - Purnomo Ajie, Lintang
It is estimated that 33% of the world's population is currently experiencing a clean water crisis. Ironically, the facts prove that of 70% of the water on the earth's surface, only 0.03% can be used as clean water. Adjustment of salt content through seawater desalination is feasible to be developed to overcome the scarcity of clean water. MD is a thermally controlled separation process, in which only vapor molecules can pass through a porous hydrophobic membrane. The MD works with the difference in feed vapor pressure. The operating temperature of the MD can be reduced to 30 oC. This technology has the potential to carry out zero liquid discharge (ZLD) desalination without producing by-products. Two main weaknesses occur in the MD process, namely the emergence of fouling and wetting. Fouling is the phenomenon of the formation of unwanted material (foulant) on the surface of the membrane pores. Fouling will make the membrane pores lose their hydrophobic properties and become wetted by the liquid. This makes the permeate contaminated by passing impurities and the product quality decreases. This phenomenon is called wetting. Fouling can be suppressed by reducing foulants that are abundant in seawater. This can be done by pretreatment using nanofiltration (NF). Fouling in MD can be suppressed by adjusting the operating temperature and permeate flow rate. Increasing the operating temperature MD will increase the flux of the membrane as the temperature polarization decreases. Increasing the permeate flow rate can increase the heat and mass transfer coefficients so that the driving force of vapor permeation along the membrane increases. Prevention of fouling and wetting in the membrane pores can also be done by modifying the membrane structure. The use of hydrophilic materials such as Nafion is projected to ensure a high flux. Research on the NF process shows that the higher the operating pressure in the NF process, the higher the membrane flux produced. The average flux for operating pressures of 4, 6, and 8 bar is 3.6, respectively; 3.8; and 3.9 LMH. There does not appear to be any particular trend that shows a correlation between the operating pressure in the NF process and the rejection of the Ca, Mg, and Na ions obtained. The best rejection profile was obtained by the process at a pressure of 5 bar with the rejection values of Ca, Mg, and Na being 65%, 65%, and 8%, respectively. Research on the MD process shows that the higher the MD operating temperature, the higher the flux value produced. The highest average flux value was obtained at a temperature variation of 70 oC and a permeate circulation rate of 0.88 m/s which reached 9.94 kg/m2hour. No clear correlation was found between the operating temperature and the conductivity of the resulting permeate. It appears that the permeate circulation rate strongly correlates with the resulting membrane flux. The higher the permeate circulation rate, the higher and/or stable the resulting membrane flux will be. The correlation between the permeate circulation rate and the resulting permeate conductivity is more difficult to determine. Overall, the effect of operating temperature and permeate circulation rate on the resulting permeate conductivity tends to be inconsistent. Research related to composite membrane fabrication showed that the variation of the 12% composite membrane gave a better anti-fouling profile than the pristine membrane and the 15% composite membrane where the flux could remain stable in the range of 5.5 to 7 kg/m2hour for 48 hours. On the other hand, the 15% composite membrane variation gave a better anti-wetting profile than the 12% composite membrane where the conductivity could be maintained stable for 30 hours of operation. However, the antiwetting profile of the pristine membrane was the best of all variations, where the permeate conductivity could be kept below 300 ?s/cm. Overall, there are obstacles to validating the existing data considering that the SEM image shows that the coating layers are not evenly distributed. The interaction between the coating layer with flux and the conductivity of the permeate cannot be stated clearly because there is a factor in the uneven distribution of the coating.